Beyond the Economy: Metropolitan Mobility and the Relevance of the Peak-Car Concept - Albertos, Juan M.; Zornoza, Carmen (European Journal of Geography, 2025)
Daily mobility in urban areas is crucial for the successful implementation of an energy transition aligned with decarbonisation and sustainability objectives. Using the case of the Valencia metropolitan area, this study examines empirical evidence to determine whether there is a decline in private car use and the conditioning factors influencing this trend. The primary data sources include car ownership and driver census data from the General Directorate of Transport (Spanish government), monthly average daily traffic data from Valencia City Council, and passenger statistics from various transport companies in the region. Urban mobility data are analysed in relation to socio-economic and territorial factors. Within the conceptual framework of the peak-car hypothesis, we present evidence suggesting a decoupling between economic trends and the evolution of motorisation and car use. This finding highlights the necessity of exploring additional influencing factors, including territorial, political, cultural, and socio-demographic dynamics. Notably, the policy shift towards more sustainable mobility, initiated a decade ago, appears to have been significantly effective. Highlights: The peak-car concept remains a useful tool for analysing mobility transitions. A decoupling process between car use and the economic cycle is underway. Public policies regulating the use of public space are the most effective, even in scenarios with limited financial resources. The recent decline in urban residential density does not appear to be a significant factor in reducing car use. The dramatic increase in public transport usage following the COVID-19 pandemic is not accompanied by the necessary public investment to expand and improve its quality.